Remodeling of left ventricular hypertrophy in elite athletes after long-term deconditioning - Pelliccia, A.; Maron, B. J.; de Luca, R.; Di Paolo, F. M.; Spataro, A.; Culasso, F. (Circulation, 2002)
Background: The clinical significance and long-term consequences of left ventricular (LV) hypertrophy associated with intensive athletic conditioning remain unresolved. Methods and Results: We prospectively evaluated 40 elite male athletes who had shown marked LV cavity enlargement of 60 mm, wall thickness of 13 mm, or both in a longitudinal fashion with serial echocardiograms, initially at peak training (age 24±4 years) and subsequently after a long-term deconditioning period (1 to 13 years; mean, 5.6±3.8). After detraining, LV cavity dimension decreased by 7% (61.2±2.9 to 57.2±3.1 mm; P<0.001), maximum wall thickness by 15% (12.0±1.3 to 10.1±0.8 mm; P<0.001), and mass normalized to height by 28% (194±25 to 140±21 g/m; P<0.001). However, individual subject analysis showed persistent substantial cavity dilatation (60 mm) in 9 athletes (22%); in contrast, wall thickness returned to normal in each athlete. Multiple regression analysis demonstrated that approximately 50% of the incomplete reduction in cavity dimension was explained by increased body weight and recreational physical activity performed during the follow-up period. No athlete had developed cardiac symptoms, impaired exercise performance, or evidence of LV dysfunction. Conclusions: LV remodeling was evident after long-term detraining, with significant reduction in cavity size and normalization of wall thickness. Resolution of cavity enlargement was, however, incomplete in most cases, and substantial chamber dilatation persisted in >20% of athletes. The possibility that this residual LV hypertrophy, apparently part of the athlete`s heart syndrome, may have future long-term clinical implications in some individuals cannot be excluded with certainty.